Pengaruh Variasi pH Dan Waktu Pada Pembuatan Bioetanol Dari Sari Kulit Nanas Dengan Menggunakan Zymomonas Mobilis - Cece R; Chairul Chairul; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bioethanol is an alternative energy source that has enough potential to replace fossil fuels. Bioethanol can be produced by fermentation of carbohydrate crops . One of the raw materials that can be used is a pineapple peel. Because today is still a waste of pineapple peel untapped. In pineapple peel contained 13.6 % reducing sugar , so as to have good potential to be processed into bioethanol . One way of making bioethanol is by microbial fermentation using Zymomonas mobilis . The fermentation process is influenced by several factors, including pH and time . This study was conducted to determine the optimum pH and time at fermentation process for bioethanol production from pineapple peel juice. The study was conducted by varying the pH of 4.5, 5.0, 5.5 and 6.0 with fermentation time 14 , 23 , 39 , 47 , 65 , and 71 hours using Zymomonas mobilis microbes . Bioethanol yield analysis using a gas chromatograph (GC). The result is the highest ethanol yield was 3.01% at pH 4.5 and fermentation time of 65 hours. Keyword: Bioethanol, zymomonas mobilis, pineapple peel, yield, GC